STRENGTHENING INDIGENOUS PEOPLES’ RIGHTS: INTEGRATING THE FPIC PRINCIPLE INTO INDONESIA'S MINING LEGAL FRAMEWORK - La Ode Dedihasriadi; Adhe Ismail Ananda; Dewi Kania Sugiharti; Arie Ekawie Baskhoro; A. Muhammad Hasgar A.S (Cepalo, 2026)
Agrarian conflicts resulting from mining permits issued without the consent of local and indigenous communities expose a legitimacy gap in Indonesia’s mining legal regime. Unequal power relations between land rights holders and IUP holders reveal structural weaknesses in the protection of collective rights. This study identifies the absence of Free, Prior, and Informed Consent (FPIC) as a core deficiency that undermines substantive justice and meaningful participation in natural resource governance. Using a normative legal approach and conceptual analysis of relevant legal instruments, the study critically examines national regulations that remain procedural, transactional, and detached from community participation. The findings show that integrating FPIC is not merely a technical adjustment, but a legal, ethical, and social necessity to shift mining governance from a licensing-based to a consent-based regime. The study contributes academically by proposing mining law reform grounded in collective rights recognition, the creation of an independent FPIC verification body, and the repositioning of communities as legal subjects of development. These findings carry important implications for legal reform oriented toward environmental justice, social legitimacy, and the sustainability of mining investment in Indonesia.